(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The study aimed to find out the effect of infection with Toxoplasma gondii and the incidence of tachycardia. With the effect of injury on the levels of creatine kinase, lactate dehydrogenase and troponin in the blood serum, from the beginning of October 2021 until the end of February 2022. 96 blood samples were taken from patients who visited the outpatient clinics of cardiologists and Samarra General Hospital. The samples were divided into three groups, the first were those with heart disease and Toxoplasma parasite, the second were those with heart disease only, and the third was the control group. The separated serum was kept at a temperature of (-20) until use. Enzyme-linked immunosorbent assay (ELISA) was used to detect toxoplasmosis. The same technique was also used to detect the levels of lactate dehydrogenase, creatine kinase and troponin. The results of the study showed a significant increase at the level of significance (P < 0.05) in the levels of (Troponin), (CK) and (LDH). In the group infected with Toxoplasma parasite compared to the control group. On the other hand, it was found that there were significant differences at a significant level (P < 0.05) in the levels of (Troponin), (CK) and (LDH) between the group infected with Toxoplasma and heart diseases with the group with heart diseases.